2009
DOI: 10.1097/aog.0b013e3181b72ebe
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Placental Pathologies as the Main Causes of Fetal Death

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
63
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 28 publications
(30 reference statements)
12
63
2
5
Order By: Relevance
“…Congenital anomalies were noted in 7.7%. Similar results were seen in study by Choudhary et al and Kortweg et al 1,4 IUFD is a tragic event for parents and a great cause of stress for caregivers. Identification of cause of IUFD will be helpful in counseling and consoling the grieving parents and alley their fear regarding future pregnancy.…”
Section: 2supporting
confidence: 80%
See 1 more Smart Citation
“…Congenital anomalies were noted in 7.7%. Similar results were seen in study by Choudhary et al and Kortweg et al 1,4 IUFD is a tragic event for parents and a great cause of stress for caregivers. Identification of cause of IUFD will be helpful in counseling and consoling the grieving parents and alley their fear regarding future pregnancy.…”
Section: 2supporting
confidence: 80%
“…Several studies have shown placental pathology as a major contributor to IUFD, hence stressing the importance of its examination. [3][4][5] Kortweg et al, included placental histopathology in the classification for the causes of perinatal deaths. 6 In present study, placental pathology was direct cause in 77% of IUFDs.…”
Section: 2mentioning
confidence: 99%
“…Congenital anomalies [41], placental infarction and abruption [42], umbilical cord abnormalities and accidents [43,44], infection [45] and maternal complications of pregnancy, such as hypertension and diabetes [46,47], are important causes of stillbirth; however, more than one quarter of stillbirths remains unexplained [10,42,48,49]. The causes of stillbirth in developed countries are considerably different than those in developing nations, because of differences in education, medical facilities, quality of life and economy [50].…”
Section: Causes Of Perinatal Mortalitymentioning
confidence: 99%
“…Korteweg и соавт. [17] были проанализированы причины антенатальной гибели плодов в Нидерландах в 750 случаях беременности после 20 нед гестации. Автора-ми указано, что главной причиной гибели плодов была плацентарная патология (64,9%), врожденные пороки развития имелись в 5,3%, инфекция -в 1,9%, другие при-чины -в 4,8% и неизвестные причины -в 23,1%.…”
unclassified
“…Автора-ми указано, что главной причиной гибели плодов была плацентарная патология (64,9%), врожденные пороки развития имелись в 5,3%, инфекция -в 1,9%, другие при-чины -в 4,8% и неизвестные причины -в 23,1%. При-чем роль плацентарной недостаточности значительно уве-личивается после 32 нед беременности (с 16,5% в сроке 20-31 нед до 77,6% в сроке после 32 нед) [17]. Обнаруже-ние выраженных патологических изменений в различных отделах последа может указывать не только на наличие и характер инфекции, но и на путь инфицирования плода или новорожденного [18].…”
unclassified